Повести и рассказы: 1848-1859 / ред. Н. Ф. Буданова - Достоевский Федор Михайлович (1988)
Экземпляры: ЧЗ (20160218) / Инвентарный номер: 21944 / Цена: 4.00 / Авт.знак: Д 70 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)1